Zinc supplementation and 60-day mortality in patients receiving total parenteral nutrition: a single-center experience - Liu, Mei-Yuan; Kuo, Chia-Yin; Lee, Hwung-Chung; Wu, Jheng-Yan (Frontiers in Nutrition, 2026)
ObjectiveZinc deficiency is common among patients receiving total parenteral nutrition (TPN) and may contribute to impaired wound healing, immune dysfunction, and adverse clinical outcomes. However, the impact of zinc supplementation on short-term survival remains unclear.MethodsWe retrospectively reviewed adult patients who received TPN at a single center between January 2019 and October 2023. Patients were categorized according to their mean daily zinc dose: < 2 mg/day or ≥2 mg/day. Patients were classified into a standard zinc supplementation group receiving approximately 6.35 mg of elemental zinc per day and an augmented zinc supplementation group receiving approximately 7.7 mg per day. Baseline characteristics, nutritional indices, and biochemical parameters were compared. The primary outcome was 60-day all-cause mortality. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazards models.ResultsA total of 1,037 patients were included (415 in the standard zinc supplementation group and 622 in the augmented zinc supplementation group). Baseline characteristics were comparable between groups (mean age 65 years; 60% male). The augmented zinc supplementation group had higher mean serum zinc concentrations (75.9 ± 22.0 μg/dl vs. 65.9 ± 27.5 μg/dL, P < 0.001). The 60-day mortality rate was significantly lower in the augmented zinc supplementation group (22.7% vs. 15.0%; HR = 0.66; 95% CI 0.50–0.88; P = 0.004). No major differences were found in caloric or protein adequacy, albumin, or C-reactive protein trends between groups.ConclusionIn this single-center retrospective cohort, higher zinc supplementation (≥2 mg/day) during TPN administration was associated with lower 60-day mortality. These findings highlight the potential clinical relevance of zinc dosing in TPN regimens and warrant prospective validation.